A fluorescence aptasensor based on carbon quantum dots and magnetic Fe3O4 nanoparticles for highly sensitive detection of 17β-estradiol. (30th March 2022) - Wei, Qingyi; Zhang, Peiyao; Pu, Hongbin; Sun, Da-Wen
Highlights: Carbon quantum dots were firstly used to detect 17 β -estradiol successfully. The aptasensor showed high sensitivity and selectivity for 17 β -estradiol detection. A low limit of detection of 3.48 × 10 -12 M was obtained. 17 β -estradiol in milk and water samples were analyzed with satisfied recovery. Abstract: Trace amounts of 17 β -estradiol (E2) in food and the environment poses a threat to human health, which has created the demand for sensitive analytical methods to detect E2. In this study, a novel fluorescent aptasensor was developed for sensitive detection of E2 based on double-chain hybridization between carbon quantum dots-labelled with E2 aptamer (CQDs-aptamer) and Fe3 O4 nanoparticles modified by complementary DNA (Fe3 O4 -cDNA). Under the optimal conditions, the aptasensor displayed a good linear range of 10 -11 –10 -6 M for E2 with the coefficient of determination (R 2 ) of 0.996, and a low detection limit of 3.48 × 10 -12 M was obtained. Besides, the aptasensor showed high selectivity and good reproducibility for E2 detection, which was successfully applied to the sensitive detection of E2 in milk as compared with tap water and lake water with satisfactory recoveries from 85.21% to 114.80%, suggesting the great significance of this aptasensor for detecting food contaminants in the food industry.